2021
DOI: 10.1186/s12885-021-08278-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of positron emission tomography in diagnosis of lateral lymph node metastases in patients with rectal Cancer: a retrospective study

Abstract: Background The presence of lateral pelvic lymph node (LLN) metastasis is an essential prognostic factor in rectal cancer patients. Thus, preoperative diagnosis of LLN metastasis is clinically important to determine the therapeutic strategy. The aim of this study was to evaluate the efficacy of preoperative positron emission tomography/computed tomography (PET/CT) in the diagnosis of LLN metastasis. Methods Eighty-four patients with rectal cancer wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A previous report showed that a cut-off value of 7 mm for lymph node short-axis diameter is a useful criterion for the diagnosis of lateral lymph node metastasis in patients with rectal cancer. Similarly, the present study showed that a 7 mm short-axis diameter was also an effective cut-off for the diagnosis of regional lymph node metastasis 17 . Several reports have described criteria of lymph node short-axis diameter for metastasis diagnosis, and the 7 mm cut-off used in this study is in keeping with these previous reports 7–9 .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…A previous report showed that a cut-off value of 7 mm for lymph node short-axis diameter is a useful criterion for the diagnosis of lateral lymph node metastasis in patients with rectal cancer. Similarly, the present study showed that a 7 mm short-axis diameter was also an effective cut-off for the diagnosis of regional lymph node metastasis 17 . Several reports have described criteria of lymph node short-axis diameter for metastasis diagnosis, and the 7 mm cut-off used in this study is in keeping with these previous reports 7–9 .…”
Section: Discussionsupporting
confidence: 78%
“…Several reports have described criteria of lymph node short-axis diameter for metastasis diagnosis, and the 7 mm cut-off used in this study is in keeping with these previous reports 7–9 . The usefulness of the lymph node SUVmax measurement for the diagnosis of lateral lymph node metastasis for patients with rectal cancer has been previously reported, with a lymph node SUVmax of 1.5 being the optimal cut-off value for this purpose 17 as used in this study. These findings collectively suggest that a lymph node SUVmax of 1.5 is a universal criterion for diagnosing lymph node metastasis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, the study found a strong correlation between the mediastinal LNM SUV max , the primary tumor SUV peak , and the occurrence of mediastinal LNM in patients with NSCLC. 35 PET–CT metabolic parameters have also been used to predict LNM in other tumors, such as vulvar cancer, 36 esophageal squamous cell carcinoma, 37 breast cancers, 38 rectal cancer, 39 and gastric cancer. 40 In addition to some similarities, differences between the findings of our study and those of previous studies were noted.…”
Section: Discussionmentioning
confidence: 99%